2015
DOI: 10.1016/j.chemosphere.2014.10.033
|View full text |Cite
|
Sign up to set email alerts
|

Bioaugmentation and its application in wastewater treatment: A review

Abstract: Bioaugmentation (the process of adding selected strains/mixed cultures to wastewater reactors to improve the catabolism of specific compounds, e.g. refractory organics, or overall COD) is a promising technique to solve practical problems in wastewater treatment plants, and enhance removal efficiency. The potential of this option can now be enhanced in order to take advantage of important advances in the fields of microbial ecology, molecular biology, immobilization techniques and advanced bioreactor design. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
158
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 371 publications
(160 citation statements)
references
References 65 publications
1
158
0
1
Order By: Relevance
“…Bioaugmentation has been studied and applied intensively in wastewater (Guo et al, 2010;Zhu et al, 2015), soil (Kuppusamy et al, 2016;Tribedi and Sil, 2013), and sediment (Ahn et al, 2008;Wang et al, 2015) treatment to solve practical problems (e.g., improve catabolism of refractory organics) and enhance removal efficiency (Herrero and Stuckey, 2015). It is seldom used in drinking water treatment, however, due to lower nutrient influent, backwash, and undefined microbial roles in the treatment system.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bioaugmentation has been studied and applied intensively in wastewater (Guo et al, 2010;Zhu et al, 2015), soil (Kuppusamy et al, 2016;Tribedi and Sil, 2013), and sediment (Ahn et al, 2008;Wang et al, 2015) treatment to solve practical problems (e.g., improve catabolism of refractory organics) and enhance removal efficiency (Herrero and Stuckey, 2015). It is seldom used in drinking water treatment, however, due to lower nutrient influent, backwash, and undefined microbial roles in the treatment system.…”
Section: Discussionmentioning
confidence: 99%
“…In such cases, the reactor may need a greater biomass concentration in the winter period than that in the summer period (Herrero and Stuckey, 2015). In addition, although the inoculant in our experiment survived in the column over the entire experimental period, previous studies also have shown a significant increase in bioreactor performance soon after bioaugmentation, with the positive effects only maintained for a short time after inoculation (Boon et al, 2000;Christian et al, 2015;Herrero and Stuckey, 2015). Hence, adding inoculants at regular intervals might be needed in actual treatment.…”
Section: Bioaugmentation Treatment Of Groundwater Containing High Mn(mentioning
confidence: 99%
“…However, most of the currently studied attached microalgae-bacteria consortia form via natural colonization, which may bring undesired microbial species (Adey et al, 2013;Shangguan et al, 2015). In recent decades, the rapid development in genetic engineering has greatly helped to identify and select the functional genes and strains for nutrient transform (Herrero and Stuckey, 2015;van Kessel et al, 2015;Courtens et al, 2016). Genetic and metabolic engineering offer the possibility for strain improvement (Lindemann et al, 2016) and synthetic biology provides innovative approaches for designing microorganisms or communities with superior catalytic abilities on recalcitrant pollutants, but with potential risks to the ecological safety (Karig, 2017).…”
Section: Ecological and Genetic Engineering Approaches For Controllinmentioning
confidence: 99%
“…Microorganisms for bioaugmentation should be competitive and compatible with the indigenous communities (Yu and Mohn, 2002). Thus, priority should be initially given to the selection and improvement of the local microbial species for a stable consortium community, since they are usually adaptive to the conditions of the target surface water (Herrero and Stuckey, 2015).…”
Section: Ecological and Genetic Engineering Approaches For Controllinmentioning
confidence: 99%
See 1 more Smart Citation